1990
DOI: 10.1111/j.1365-2796.1990.tb00209.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of nicotinic acid on serum cholesterol concentrations of high density lipoprotein subfractions HDL2, and HDL3, in hyperlipoproteinaemia

Abstract: Nicotinic acid was given in a 4-g daily dose for 6 weeks to 41 weight-stable patients of mean age (+/- SD) 52 +/- 9 years, with type IIa, type IIb or type IV hyperlipoproteinaemia (HLP), in order to study its effects on serum cholesterol concentrations of high density lipoprotein (HDL) subfractions HDL2 and HDL3. The triglyceride and cholesterol levels of serum very low density (VLDL) and low density (LDL) lipoproteins decreased during treatment (P less than 0.001). Serum HDL and HDL2 cholesterol levels increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 20 publications
(5 reference statements)
0
9
0
Order By: Relevance
“…High‐dose NA (above 50 mg) is marketed in the United States as a dietary supplement (which may not make drug claims) and also as a prescription drug (which may make approved therapeutic claims). The beneficial lipid‐lowering effects of both NA and ER‐NA are well established, with data showing reduction of total triglyceride levels by 20–50%, reduction of LDL‐C levels by 10–25%, increases of HDL‐C levels by 10–30%, and reduction of lipoprotein a levels by 10–30%, 30–35 which includes preferential reduction of the more atherogenic, small, dense LDL‐C 36 . Both NA and ER‐NA are effective in treating a range of lipid disorders, but neither has become a first‐line therapy because of the uncomfortable flushing side effect and the potential risk of liver and gastrointestinal side effects.…”
Section: Beneficial Effectsmentioning
confidence: 99%
“…High‐dose NA (above 50 mg) is marketed in the United States as a dietary supplement (which may not make drug claims) and also as a prescription drug (which may make approved therapeutic claims). The beneficial lipid‐lowering effects of both NA and ER‐NA are well established, with data showing reduction of total triglyceride levels by 20–50%, reduction of LDL‐C levels by 10–25%, increases of HDL‐C levels by 10–30%, and reduction of lipoprotein a levels by 10–30%, 30–35 which includes preferential reduction of the more atherogenic, small, dense LDL‐C 36 . Both NA and ER‐NA are effective in treating a range of lipid disorders, but neither has become a first‐line therapy because of the uncomfortable flushing side effect and the potential risk of liver and gastrointestinal side effects.…”
Section: Beneficial Effectsmentioning
confidence: 99%
“…Several studies have confirmed this observation in patients with different types of dyslipidemia treated with 2, 3, or 4 g/day of regular or ER niacin (Johansson and Carlson 1990;Knopp et al 1998;Morgan et al 2003;Wahlberg et al 1990) and in patients with coronary artery disease (Kuvin et al 2006). A very recent study showed that also 1 g/day of ER niacin increases large HDL particles in dyslipidemic patients, with a concomitant significant increase in mean HDL size (Franceschini et al 2013).…”
Section: Niacinmentioning
confidence: 53%
“…In contrast to fibrates, nicotinic acid exerts a larger effect on HDL 2 than HDL 3 [57][58][59]. Conversely these agents are less potent than fibrates in reducing triglyceride levels with reductions generally around 20%.…”
Section: Nicotinic Acid Derivativesmentioning
confidence: 93%